Needs and Considerations in Developing a Module for Hajj and Umrah for Pilgrims - Mohd Sollah Mohamed; Razimi Zakaria; Muhammad Luqman Ibnul Hakim Mohd Saad; Mohd Baharim Mayidin (Advances in Humanities and Contemporary Studies, 2023)
Arabic studies are gaining popularity not just in Malaysia but also around the world. Numerous initiatives are taken by scholars to ensure that Arabic can be learned through various methods. This study specifically aims to examine the effectiveness of the Arabic language for the purpose of Hajj and Umrah using an Arabic Language Module. The objective of studying Arabic for the purpose of Hajj and Umrah is apt due to the growing interest among Muslim adults. This module has a clear objective which is to encourage Hajj and Umrah pilgrims to learn Arabic as to enhance the quality in the performance of Hajj and Umrah. It also aims to improve the value of worship among the Hajj and Umrah pilgrims. The study concludes with a proposal for the application of the Arabic language module to enhance understanding in aspects of worshipping.